Anticholinergic drug use in Older People: A Population- Based Study in Iran - Kimia Raei; Atena Rahimi; Seyed Reza Hosseini; Ali Akbar Moghadamnia; Ali Bijani (Caspian Journal of Internal Medicine, 2021)
Background: Elderly people are in need of several drugs due to physiological changes and multiple chronic diseases. Studies have shown that anticholinergic drugs can cause cognitive impairment, reduced physical activity, and increased mortality in elderly population. Paying attention to the anticholinergic medication use in older adults can prevent the occurrence of adverse events and increase the quality of health care. This study was conducted to quantify exposure to anticholinergic medicines in older people in Amirkola. Methods: This study is a part of the comprehensive cohort project that was being conducted from 2011 on the case patients of 60 years and above that referred to the Amirkola Health Center. A total of 1532 individuals were included, of whom 54.9% were men. The drug information was obtained by observing the patient’s prescription and self-report questionnaires and collected data were analyzed by SPSS software. Exposure to anticholinergic medications was measured using the drug burden index-anticholinergic (DBI-Ach) and the anticholinergic drug scale (ADS). Results: Among the 1532 elderly people with an average age of 69.21 years, 29% had DBI>0 and 36.3% had ADS>0. Also, there was a significant correlation between DBI and ADS (R=0.758). In addition, there is a significant relationship between sex variable with DBI and ADS (P=0.0001). So, women in comparison with men had higher values of DBI and ADS. Conclusion: The findings of this study indicate that anticholinergic exposure is relatively high especially in older women, which posed special precautions to avoid inappropriate prescribing in the elderly.